Bersama Cegah Anemia : Pemberdayaan Remaja dalam Kampanye Gizi dan Pola Hidup Sehat - Nastitie Cinintya Nurzihan; Ratih Wirapuspita Wisnuwardani; Nurul Afiah; Indria Pijaryani; Leny Eka Tyas Wahyuni; Akhmad Dzikri (Poltekkes Kemenkes Surakarta, 2025)
Background: Anemia remains a significant public health issue among adolescent girls in Samarinda, with a reported prevalence of 20.3%. The condition, often linked to iron deficiency, poses risks to physical development, cognitive performance, and overall well-being. Contributing factors include unbalanced dietary habits, menstruation, parasitic infections, and low awareness of nutritional needs. This activity aims to enhance the capacity of adolescents to prevent anemia through participatory and sustainable nutrition campaigns and healthy lifestyle practices. Methods: This community service initiative was conducted at SMA Negeri 1 and SMA Negeri 10 Samarinda from November 15-21, 2024, involving 40 female students. A participatory and educational approach was employed, including group discussions, health counseling, and the use of visual educational media such as booklets and PowerPoint presentations. Pre- and post-tests were administered to evaluate changes in knowledge. Results: The participants, predominantly aged 16 years, showed low baseline awareness about anemia. The intervention led to a 22% increase in knowledge regarding the causes, symptoms, and prevention of anemia. Interactive discussions and visual media effectively engaged students, promoting better understanding and proactive attitudes toward healthy lifestyles and iron intake. Conclusion: A participatory and visual-based approach is effective in promoting health knowledge and behavior change among adolescents, with potential long-term benefits for school and community health. Recommended activities include interactive nutrition education sessions, visual media campaigns, peer-led discussions, and community-based monitoring to sustain behavior change.